RISK OF HELMINTHIASIS IN PREGNANT WOMEN - Rio Khoirudin Apriyadi; M Taufan Umasugi; Endah Fitriasari (Jurnal Multidisipliner Bharasa, 2022)
The helminthic disease is transmitted through the soil that causes the human body to become infected with worms. Worms can lead to a deterioration in the state of health, nutrition, intelligence, and productivity of the infected individual. This study aims to discover how worms affect pregnant women's condition of the child to be born or the baby. This research uses a normative or literature approach, with the primary data source as documents related to the research subject. Data analysis was carried out descriptively. The results showed that worms in pregnant women affect the condition of the child to be born or the baby, such as the risk of prematurity, low birth weight, and the risk of perinatal death because helminth infections can cause anemia due to the body losing iron deposits which will eventually interfere with the formation of hemoglobin which is due to a decrease in food intake and malabsorption of nutrients. Abstrak Pesantren dalam catatan sejarah memainkan peran penting dalam dunia pendidikan, ekonomi dan politik. Ekonomi pesantren pada dasarnya telah mempersiapkan diri sebagai independensi organisasi dalam mempertahankan eksistensinya. Peraturan Kemenag mengisyaratkan independensi pesantren dengan roadmap kemerdekaan sebagai pedoman utama. Sementara itu, UU Pesantren belum secara spesifik menyebutkan hal tersebut. Tulisan ini berupaya menjelaskan pelaksanaan independensi pesantren dan perlunya rekonstruksi UU Pesantren dalam perspektif pesantren m andirian. Penelitian ini menggunakan pendekatan kepustakaan. Hasil penelitian menunjukkan perlunya wacana rekonstruksi pasal-pasal dalam UU Pesantren sejalan dengan program kemandirian pesantren dan program atau teknis pelaksanaan di bawahnya, mulai dari pendanaan pesantren, roadmap kemandirian pesantren, hingga petunjuk teknis bantuan usaha pesantren.